Deciphering differences in microbial community characteristics and main factors between healthy and root rot-infected Carya cathayensis rhizosphere soils - Fang, Wei; Zhu, Yiyang; Liang, Chenfei; Shao, Shuai; Chen, Junhui; Qing, Hua; Xu, Qiufang (Frontiers in Microbiology, 2024)
IntroductionFusarium-induced root rot of Carya cathayensis (C. cathayensis) is a typical soil-borne disease that has severely damaged the Carya cathayensis industry in China. Understanding the interaction among soil microbial communities, soil characteristics, and pathogenic bacteria is very important for the ecological prevention and control of Carya cathayensis root rot.MethodsWe used Miseq Illumina high-throughput sequencing technology to study the microbial community in the rhizosphere soil of healthy and diseased C. cathayensis, quantified the abundance of bacteria, fungi, and pathogenic fungi, and combined these with soil chemistry and enzyme activity indicators to analyze the characteristics of healthy and diseased rhizosphere soils.ResultsWe found that the pH, soil organic carbon(SOC), available nitrogen (AN), available phosphorus (AP), available potassium (AK),N-acetyl-β-D-glucosaminidase (NAG) β-glucosidase (BG), fungal gene copy number, bacterial community diversity and network complexity of the diseased soil were significantly lower (p < 0.05), while Fusarium graminearum copies number levels increased (p < 0.05). Additionally, the study found that healthy soils were enriched with beneficial bacteria such as Subgroup_7 (0.08%), MND1 (0.29%), SWB02 (0.08%), and Bradyrhizobium (0.09%), as well as potential pathogen-suppressing fungi such as Mortierella (0.13%), Preussia (0.03%), and Humicol (0.37%), were found to be associated with the growth and development of C. cathayensis.DiscussionIn summary, this research comprehensively reveals the differences in environmental and biological factors between healthy and diseased soils, as well as their correlations. It provides a theoretical basis for optimal soil environmental regulation and the construction of healthy microbial communities. This foundation facilitates the development of multifaceted strategies for the prevention and control of C. cathayensis root rot.